Beyond plucking: Feathers bioprocessing into valuable protein hydrolysates. (15th July 2019) - Callegaro, Kelly; Brandelli, Adriano; Daroit, Daniel Joner
Graphical abstract: Highlights: Keratin-rich wastes are recalcitrant and abundant biomasses from meat production. Increased focus on the conversion of residual biomasses into protein hydrolysates. Hydrolysates are claimed for agriculture, and feed and biofuels production. Bioactive hydrolysates and peptides have potential positive effects on human health. Production of valuable products considering the human-environment relationship. Abstract: The livestock production and subsequent processing of meat results in huge quantities of solid waste such as viscera, bones, skin and keratin-rich materials, including feathers, hair, wool, claws and hooves. In particular, the continuous growth of poultry industry generates massive amounts of feathers as major waste material. The conversion of such by-products into materials with increased value has been studied. Hydrothermal, chemical or biological approaches have been investigated to achive effective conversion of highly recalcitrant proteins that are abundant in animal waste, but increasing interest is devoted to the development of biotechnological methods. The processing of feathers and other by-products into protein hydrolysates may have industrial and commercial significance. Therefore, this review comprehensively addresses the postulated applications of hydrolysates obtained from keratinous biomasses. Examples on the utilization of feather hydrolysates as organic soil fertilizers, feed ingredients, cosmetic formulations and biofuel production are described in the literature. Microbial feather hydrolysis can generate bioactive peptides as well. The use of protein-rich waste from meat industry to produce hydrolysates with biological activities constitutes a point of utmost interest for development of functional ingredients with elevated value.